EFFECTS OF ELECTROMAGNETICS RADIATION EXPOSURE ON HEMATOLOGIC DISORDERS OF PEOPLE LIVING NEAR HIGH VOLTAGE OVERHEAD POWER LINE - Khoerunisa, Rahmi
High Voltage Overhead Power Line is one of many artificial sources of electromagnetics radiation. According to WHO, electromagnetics field have the potential to cause health problems for human and tend to cause cancer. Cross-sectional research conducted to determine the risk of hematologic disorders following residential exposure from 150 kV overhead power line. As many as 32 women who live 10 meters from power line are compared with 21 women who live more than 400 meters from the power line. Respondents are selected by questionnaire and interview. Electromagnetics exposure level obtained by the measurement at morning and evening. Hematologic parameters evaluated including erythrocytes, hemoglobin, hematocrit, MC values, differential white cell count, platelet count and erythrocytes sedimentation rate. Respondent’s body height and weight also measured to calculate Body Mass Index as the nutrition status variable. Electromagnetics exposure analysis conducted using box plot diagram and t-test. The risks of hematologic disorders are determined using logistic regression analysis based on exposure and nutrition status variables. Maximum level of exposure for electric and magnetic field in exposed group are 48 V/m and 5,1 ?T, while maximum exposure of controlled group are 52 V/m and 0,27 ?T. whole level of electric and magnetic fields exposure still comply with health standard that is recommended by WHO. Exposure that considerably affects the hematologic disorders is magnetic field exposure. According to logistic regression analysis, there are no hematologic disorders that have significantly association with electromagnetic exposure and nutrition status variables. Hematologic disorders that have higher Odd Ratio value based on exposure variable are the lack of hemoglobin concentration (OR = 2,134, p = 0,439), low MCV value (OR = 4,349, p = 0,089), low MCH value (OR = 3,959, p =0,135) and high erythrocytes sedimentation rate (OR = 2,609, p = 0,166). The hematologic disorders that are considerably influenced by magnetic field exposure from power line are microcytic condition and the lack of hemoglobin in erythrocytes.